Optimized approach to retrieve information on atmospheric carbonyl sulfide (OCS) above the Jungfraujoch station and change in its abundance since 1995. (January 2017) - Lejeune, Bernard; Mahieu, Emmanuel; Vollmer, Martin K.; Reimann, Stefan; Bernath, Peter F.; Boone, Christopher D.; Walker, Kaley A.; Servais, Christian
Abstract: In this paper, we present an optimized retrieval strategy for carbonyl sulfide (OCS), using Fourier transform infrared (FTIR) solar observations made at the high-altitude Jungfraujoch station in the Swiss Alps. More than 200 lines of the ν3 fundamental band of OCS have been systematically evaluated and we selected 4 microwindows on the basis of objective criteria minimizing the effect of interferences, mainly by solar features, carbon dioxide and water vapor absorption lines, while maximizing the information content. Implementation of this new retrieval strategy provided an extended time series of the OCS abundance spanning the 1995–2015 time period, for the study of the long-term trend and seasonal variation of OCS in the free troposphere and stratosphere. Three distinct periods characterize the evolution of the tropospheric partial columns: a first decreasing period (1995–2002), an intermediate increasing period (2002–2008), and the more recent period (2008–2015) which shows no significant trend. Our FTIR tropospheric and stratospheric time series are compared with new in situ gas chromatography mass spectrometry (GCMS) measurements performed by Empa (Laboratory for Air Pollution/Environmental Technology) at the Jungfraujoch since 2008, and with space-borne solar occultation observations by the ACE-FTS instrument on-board the SCISAT satellite, respectively, and they show good agreement. The OCS signal recorded above Jungfraujoch appears to be closely related to anthropogenic sulfur emissions. Highlights: An approach for retrieving OCS from ground-based infrared spectra is presented. The OCS trend over 1995–2015 is characterized. A non-monotonic long-term evolution of OCS with time is observed. Comparison with satellite and in situ surface measurements is included.